LEGAL ORIGINS OF FREEDOM OF ECONOMIC ACTIVITY - Juškevičiūtė-Vilienė, Agnė (Teisė, 2015)
This article reveals historical circumstances of how the freedom of economic activity was formed and how it was incorporated into the Lithuanian constitutional law. The article indicates and describes general global circumstances that formed the freedom of economic activity (considering the influence of mercantilism), and it focuses on the more significant ideas of the classical liberal theory of economics that influenced the emergence of economic freedom the most positively. After discussing the formation of economic freedom in the world, the article describes circumstances that influenced its entrenchment in the Lithuanian constitutional law after the restoration of independence. The study showed that after the restoration of independence in the Republic of Lithuania, there was a need for the new Constitution, which was dictated by statehood, democracy, and free-market. The variety of Constitution projects by the Supreme Council of the Republic of Lithuania, various political parties, associations, and academics shows that there were various opinions on the structure of state and the legal status of an individual. However, thoughts on economic freedom were the same: it was intended to guarantee freedom for economic entities in order to choose and engage in economic activity, and the state should execute a protective function – to regulate the process of economic activity in such way, so that it would guarantee its freedom – rather than regulate the market. Considering the ideas of economic liberalism, the Constitution of 1992 emphasized limited constitutional power the state government in the field of economy, determining its competencies, constitutional balance, and cooperation with economic entities; it constitutionally entrenched rights and freedoms of economic entities, their defense methods.